Certificateless Key-Insulated Generalized Signcryption Scheme without Bilinear Pairings. (2nd August 2017) - Zhou, Caixue; Zhao, Zhiqiang; Zhou, Wan; Mei, Yuan
Abstract : Generalized signcryption (GSC) can be applied as an encryption scheme, a signature scheme, or a signcryption scheme with only one algorithm and one key pair. A key-insulated mechanism can resolve the private key exposure problem. To ensure the security of cloud storage, we introduce the key-insulated mechanism into GSC and propose a concrete scheme without bilinear pairings in the certificateless cryptosystem setting. We provide a formal definition and a security model of certificateless key-insulated GSC. Then, we prove that our scheme is confidential under the computational Diffie-Hellman (CDH) assumption and unforgeable under the elliptic curve discrete logarithm (EC-DL) assumption. Our scheme also supports both random-access key update and secure key update. Finally, we evaluate the efficiency of our scheme and demonstrate that it is highly efficient. Thus, our scheme is more suitable for users who communicate with the cloud using mobile devices.